Development of Android-based Application for Mental Health Services in Butuan City, Philippines - Plender-Nabas Jenie L.; Mulig Edzel; Olvido Desiree (SHS Web of Conferences)
This study aimed to develop and evaluate an Android-based mobile application relative to mental health services in Butuan City to address challenges faced by both clients seeking mental health services, and mental health service providers who are also trying to reach clients and patients in need of their services. This mobile application functions as an intermediary platform, allowing clients to conveniently search for mental health service providers, schedule appointments, and locate their physical office addresses. For mental health service providers, the application offers appointment management modules and service management, streamlining their workflow and potentially reducing administrative burdens such as scheduling and other workloads. To evaluate the effectiveness of the mobile application in addressing the identified challenges, a survey was conducted among 100 respondents within Butuan City, including potential clients and mental health service providers. The survey results yielded an Excellent rating which indicates a strong level of agreement among the respondents regarding the application’s usability suggesting that users perceive that the mobile application is a user-friendly and intuitive platform. Qualitative feedback obtained during the usability study highlighted the application’s value in addressing current challenges faced by both clients and mental health service providers. Future researchers may also consider to include other stakeholders, such as the local government units, in the promotion and further development of the mobile application for it to contribute and support regulatory decisions related to mental health or the integration of mental health apps into the healthcare systems of the country in general.